Hermann Giliomee, Historian: An Autobiography (Historia, 2021)
The late John Clive, author of the outstanding biography Macaulay: The Shaping of the Historian, suggested that rather than studying dense theories on historiography, students should read the works and study the lives of great historians. These books,he suggested, would provide measure and inspiration for them. Clive was convinced that there is something uniquely instructive for the apprentice historian to be taken into a great historian’s workshop, observing him or her labouring with the rawmaterials. They would then realise, wrote Clive, that even the greatest masters of the craft struggle, because the writing of history is hard work at any level.5 Historian: An Autobiography would have gladdened Clive’s heart because Hermann Giliomee makes it possible for students to enter his “workshop” and observe his guiding principles and methodology as he writes about the past in a period of turmoil, violence and dramatic political change in South Africa.
Keywords: John Clive; history; Afrikaner; nationalism; Giliomee